Clarke duality for Hamiltonian systems with nonstandard growth. (November 2019) - Acinas, S.; Maksymiuk, J.; Mazzone, F.
Abstract: We consider the existence of periodic solutions to Hamiltonian systems with growth conditions involving G-function. We introduce the notion of symplectic G-function and provide relation for the growth of Hamiltonian in terms of certain constant C G associated to symplectic G-function G . We discuss an optimality of this constant for some special cases. We also provide applications to the Φ -laplacian type systems.